Integrating Libraries to Electronic Health Record Systems - Küyük, Ayşen; Kaplan, Aslan; Yılmaz, Ali (Information World, 2005)
The increase of volume and variety of information, which in turn has an important role in health services, reached to an explosive bulk, that can hardly be managable for the users. In order to meet users’ needs under these conditions, electronic health record systems were developed. Electronic health record systems integrated with electronic libraries allow clinicians, along with the patient information, also to access medical literature they would need for treatment. By comparing patient information with current information sources concerning relevant medical advances and thus performing evaluations being based on such comparisons help clinicians to save time and make fast and accurate decisions. On the other hand, the use of electronic health record systems require more active roles from medical libraries and their librarians within the framework of their parent organisation.